How cultural tightness relates to creativity in work teams: Exploring the moderating and mediating mechanisms - Gedik, Yeliz; Ozbek, Mehmet Ferhat (Wiley, 2020)
In the present study, we examined the team-level association between cultural tightness, justice and creativity under varying levels of collectivism. Utilizing data from a field sample of 532 employees distributed across 147 work teams in 13 organizations, we demonstrated that cultural tightness was negatively related to team creativity for teams with lower levels of collectivism, but we did not observe such clear effects in teams with higher levels of collectivism. Finally, our results indicated that team justice climate (i.e., the average justice perception within the team) mediated the relationship between cultural tightness and team creativity in teams with lower levels of collectivism. Our findings accentuate the importance of understanding how norm-based (i.e., cultural tightness) and value-based (i.e., team collectivism) cultural dimensions jointly impact upon team creativity and suggest that managers should consider the optimal configuration of cultural dimensions if creativity is vital to their work team's functioning.
Keywords: cultural tightness; team collectivism; team creativity; team justice climate